THE IMPACT OF PHYSICAL ACTIVITY ON THE HEALTH OF PREGNANT WOMEN AND FETAL AND NEONATAL DEVELOPMENT - A LITERATURE REVIEW - Aleksandra Sokół,; Karolina Glajcar,; Remigiusz Flakus,; Żaneta Kania,; Weronika Perczyńska,; Gabriela Kapłon,; Dominika Gieroba,; Julia Szczotka,; Gabriela Szpila,; Anna Kamieniak,; Artur Tumiński,; Marianna Chmiel, (International Journal of Innovative Technologies in Social Science, 2025)
Introduction: Physical activity during pregnancy is attracting increasing interest among women, doctors and researchers. In recent years, there has been a growing body of research highlighting the positive effects of physical activity during this period. Contrary to earlier beliefs, physical activity is not only safe, but also recommended. The aim of this review is to analyse the current scientific evidence on the safety and benefits of exercise during pregnancy and to provide recommendations on the type and intensity of activity.Methods: A comprehensive search of the scientific literature was conducted using PubMed and Google Scholar, taking into account publications published since 2017. Keywords included: "physical activity", "pregnancy", "healthy pregnant woman", "exercise" and "pregnant exercises".Conclusions: A review of the scientific literature from the last eight years shows that regular, moderate physical activity has a number of health benefits for mother and baby, provided there are no medical contraindications. Promoting individualized, supervised exercise and education for both expectant mothers and healthcare providers should be a key element of prenatal care.